The Impact of Information About the Female Condom on Female Condom Use Among Males and Females from a US Urban Community. - Coman, Emil N; Weeks, Margaret R; Yanovitzky, Itzhak; Iordache, Eugen; Barbour, Russell; Coman, Maria A; Huedo-Medina, Tania B (AIDS and behavior, 2012)
This study investigates the impact of exposure to information about a relatively new prevention method, the female condom (FC), on actual FC use in a community of adults at risk of HIV/STI. A community-wide survey from a mid-size US city is used to estimate unbiased effects of information about the FC on FC use among sexually active men and women. To control for potential confounders we use propensity score matching (PSM) which matches the group exposed to FC information to participants who were not exposed, achieving a statistical quasi-randomization in terms of ten measured confounders. Comparisons of exposed to unexposed participants matched on their propensity scores conclude that information about the FC increases initiation of FC use, such that eleven percent more of the men and women who receive FC information reported ever using the FC. We demonstrate the use of PSM and illustrate some of its strengths and limitations.